Energy-saving low-temperature photocuring powder coating
By grafting triphenylmethane triisocyanate on the polyacrylate molecular chains, the interaction between the polymeric molecular chains is reduced, and the problem of high melt viscosity of powder coatings when cured at low temperatures is solved, and better coating film leveling and surface effect is achieved.
Patent Information
- Application Number
- CN202510135152.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-29
AI Technical Summary
When existing powder coatings cure at low temperatures, the melt viscosity of the resin is high, which makes it difficult for the coating film to level and affects the surface effect.
Using reactive polymers with pendant groups, by grafting tritylmethane triisocyanate molecules on the polyacrylate molecular chains, the interaction between the polymeric molecular chains is reduced, and the degree of crystallization is reduced, thereby reducing the melt viscosity of the resin.
A lower melt viscosity of the resin at lower temperatures is achieved, and the leveling property and surface effect of the coating film are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder coatings, and in particular relates to an energy-saving, low-temperature light-curing powder coating. Background Art
[0002] Powder coating is a kind of coating that is applied in powder form. No solvent is needed in the production and construction process. It has the significant advantage of low volatile organic compound (VOC) emissions and minimal impact on human health and the environment. It is highly favored for its non-toxic and environmentally friendly characteristics. Among them, powder coating that can be cured at low temperature not only helps to reduce energy consumption, but is also suitable for substrates that are not resistant to high temperatures, such as plastics and wood, further expanding the application field of powder coating.
[0003] However, it is technically difficult to achieve ultra-low temperature curing of powder coatings: the resin has a high melt viscosity at low temperatures, which makes it difficult for the coating to flow smoothly during low temperature curing, thus affecting the surface effect. In order to reduce the low temperature melt viscosity of the curing resin, a common method is to synthesize dendritic and hyperbranched semi-crystalline polymers as low temperature curing unsaturated resins. However, the preparation process of such resins is often more complicated and the preparation process is longer. When the side chains are too long, there is a risk of entanglement, which will also affect the fluidity of the resin. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an energy-saving low-temperature light-curing powder coating, which comprises, by weight:
[0005] 100 parts of reactive polymer grafted with side groups
[0006] Leveling agent 0.5~2 parts
[0007] 0.2-1 part of UV absorber
[0008] Defoaming agent 0.2~0.5 parts
[0009] 1 to 3 parts of photoinitiator,
[0010] Among them, the preparation method of the reactive polymer grafted with side groups is as follows: first, the acrylate monomer, the first functional acrylic monomer, the free radical initiator, and the chain transfer agent are fully mixed to form a uniform mixed solution. Then, the mixed solution is added dropwise to the first solvent to carry out a polymerization reaction. After the polymerization reaction is carried out for a period of time, an excess of triphenylmethane triisocyanate and the first catalyst are added to the first solvent to carry out a grafting reaction. After the grafting reaction is completed, the first separation and purification operation is carried out, and the obtained intermediate product is fully washed with a suitable solvent to remove impurities. Then, the washed intermediate product is dispersed in a second solvent, and a second functional acrylic monomer and a second catalyst are added to the second solvent to continue the reaction. After the reaction is completed, a second separation and purification is carried out, and the obtained resin product is fully washed and dried to obtain a reactive polymer grafted with side groups.
[0011] The following are the preferred conditions for each component and reaction conditions:
[0012] Acrylate monomer: preferably n-butyl acrylate, methyl methacrylate or butyl methacrylate;
[0013] The first functional acrylic monomer: preferably acrylic acid, glycidyl methacrylate or hydroxy acrylate. In the molecular structure of this type of monomer, in addition to the carbon-carbon double bond involved in polymerization, it also has a group (such as hydroxyl group) that can react with isocyanate, so that it can react with triphenylmethane triisocyanate to achieve grafting;
[0014] The second functional acrylic monomer: preferably acrylic acid, glycidyl methacrylate or hydroxy acrylate. These monomers use their functional groups (such as hydroxyl groups, etc.) to react and connect with the remaining isocyanate groups on the triphenylmethane triisocyanate grafted on the polyacrylate molecular chain, thereby introducing a carbon-carbon double bond to achieve a light-curing reaction when the coating film is formed;
[0015] Molar ratio: the molar ratio between the acrylate monomer, the first functional acrylic monomer and triphenylmethane triisocyanate is preferably (2-10):1:(1.1-1.2); the molar ratio between the first functional acrylic monomer and the second functional acrylic monomer is preferably 1:(2-3.5);
[0016] Reaction temperature and time: The polymerization temperature is preferably 65°C-85°C, and the reaction time is 5-10 hours; the grafting temperature is preferably 50°C-65°C, and the reaction time is 0.5-1.5 hours; the temperature for adding the second functional acrylic monomer and the second catalyst to react is preferably 50°C-65°C, and the reaction time is 0.5-1.5 hours;
[0017] Coating preparation operation: The preparation method of energy-saving low-temperature light-curing powder coating is to fully mix the reactive polymer grafted with side groups, leveling agent, ultraviolet light absorber, defoamer and photoinitiator. Among them, the reactive polymer grafted with side groups needs to be crushed to 150-200 mesh before mixing.
[0018] The beneficial effects of the present invention are as follows: a polyacrylate molecular chain mainly composed of a linear straight chain structure is first obtained through free radical polymerization, and it is hoped that by grafting a large-volume side group on the molecular chain, the interaction between the polyacrylate molecular chains is reduced and the degree of crystallization is reduced, so that the resin mainly composed of the polyacrylate has a lower melt viscosity at a lower temperature, so as to obtain better film-forming leveling properties.
[0019] Specifically, in this scheme, triphenylmethane triisocyanate molecules are selected as grafted materials. There are three benzene rings in the molecular structure of triphenylmethane triisocyanate, and these three benzene rings are connected to the same carbon atom to form a stable three-dimensional structure. After such a three-dimensional structure is grafted onto the polyacrylate molecular chain, not only effective steric hindrance is formed between the molecular chains, but also the three benzene rings in the three-dimensional structure restrict each other, resulting in that the benzene rings on different polyacrylate molecular chains are not prone to π-π interactions, thereby effectively reducing the arrangement order between the polyacrylate molecular chains, thereby reducing the melt viscosity of the polyacrylate resin, and making it have more ideal leveling properties when cured at low temperatures. DETAILED DESCRIPTION
[0020] Example 1
[0021] Preparation of reactive polymers grafted with side groups:
[0022] 50g of methyl methacrylate, 8g of n-butyl acrylate, 11g of hydroxyethyl acrylate, 1g of azobisisobutyronitrile, and 0.5g of n-octyl mercaptan were uniformly mixed at room temperature (25°C, the same below) to obtain a monomer mixture; in a nitrogen atmosphere, 1200g of toluene was first heated to 65°C in a water bath, and then the monomer mixture was added dropwise to the toluene under a heat preservation and stirring state, and the dripping was completed in 30 minutes. After the dripping was completed, the polymerization reaction was continued for 9 hours by heat preservation and stirring. After 192g of a chlorobenzene solution of 4,4,4-triphenylmethane triisocyanate with a solute mass fraction of 20% and 0.1g of dibutyltin dilaurate were added to the obtained reaction system at one time, and the grafting reaction was continued at 50°C under a nitrogen atmosphere and a heat preservation and stirring state for 1 hour, and then the reaction system was cooled to room temperature and allowed to stand for 24 hours. The resin product in the obtained reaction system was precipitated and precipitated from the solvent, and the resin product was filtered out and fully washed with toluene as an intermediate product;
[0023] The intermediate product obtained above was added to 1000 g of toluene, and heated to 55° C. in a water bath with stirring in a nitrogen atmosphere until the intermediate product was fully dissolved. Then, 25 g of hydroxyethyl acrylate, 0.1 g of dibutyltin dilaurate, and 0.1 g of p-hydroxyanisole (inhibitor, the same below) were added thereto. The mixture was continued to react for 45 minutes at 55° C. in a nitrogen atmosphere with stirring. The mixture was cooled to room temperature and allowed to stand for 24 hours. The resin product in the reaction system was precipitated from the solvent. The resin product was filtered out and fully washed with ethanol. After being fully dried at 80° C., a reactive polymer grafted with a side group was obtained.
[0024] Preparation of energy-saving low-temperature light-curing powder coatings:
[0025] After the reactive polymer grafted with side groups prepared above in this embodiment is crushed to 180-200 meshes, 100 parts of the reactive polymer grafted with side groups, 2 parts of leveling agent BYK-358N, 0.5 parts of ultraviolet light absorber UV-360, 0.5 parts of DF360 defoamer, and 1 part of free radical photoinitiator benzophenone are added to a high-speed stirrer at 900 rpm and stirred for 30 minutes.
[0026] Example 2
[0027] Preparation of reactive polymers grafted with side groups:
[0028] 40 g of methyl methacrylate, 20 g of n-butyl methacrylate, 24 g of hydroxyethyl methacrylate, 1.2 g of azobisisobutyronitrile, and 0.5 g of n-octyl mercaptan were uniformly mixed at room temperature to obtain a monomer mixture; in a nitrogen protective atmosphere, 1500 g of toluene was first heated to 70° C. in a water bath, and then the monomer mixture was added dropwise to the toluene under a heat preservation and stirring state, and the dripping was completed in 35 minutes. After the dripping was completed, the polymerization reaction was continued for 8 hours by heat preservation and stirring, and 390 g of a chlorobenzene solution of 4,4,4-triphenylmethane triisocyanate with a solute mass fraction of 20% and 0.1 g of dibutyltin dilaurate were added to the obtained reaction system at one time, and the grafting reaction was continued at 50° C. in a nitrogen protective atmosphere with a heat preservation and stirring state for 1 hour, and then the reaction system was cooled to room temperature and allowed to stand for 24 hours. The resin product in the obtained reaction system was precipitated and precipitated from the solvent, and the resin product was filtered out and fully washed with toluene as an intermediate product;
[0029] The intermediate product obtained above was added to 1500g of toluene, and heated to 55°C in a water bath with stirring in a nitrogen protective atmosphere until the intermediate product was fully dissolved. Then, 50g of hydroxyethyl acrylate, 0.1g of dibutyltin dilaurate and 0.1g of p-hydroxyanisole were added thereto, and the mixture was continued to react at 55°C with stirring in a nitrogen protective atmosphere for 1 hour. The mixture was cooled to room temperature and allowed to stand for 24 hours. The resin product in the resulting reaction system was precipitated from the solvent. The resin product was filtered out and fully washed with ethanol, and then fully dried at 80°C to obtain a reactive polymer grafted with a side group.
[0030] Preparation of energy-saving low-temperature light-curing powder coatings:
[0031] After the reactive polymer grafted with side groups prepared in the above embodiment is crushed to 180-200 meshes, 100 parts of the reactive polymer grafted with side groups, 1.5 parts of leveling agent BYK-358N, 0.8 parts of ultraviolet light absorber UV-360, 0.4 parts of DF360 defoamer, and 1.3 parts of free radical photoinitiator benzophenone are added to a high-speed stirrer at 900 rpm and stirred for 30 minutes.
[0032] Comparative Example 1
[0033] When preparing a reactive polymer grafted with side groups, "triphenylmethane triisocyanate" is replaced with an equal molar amount of "toluene-2,4-diisocyanate (2,4-TDI)", and the remaining components and operations are the same as in Example 1:
[0034] Preparation of reactive polymers grafted with side groups:
[0035] 50 g of methyl methacrylate, 8 g of n-butyl acrylate, 11 g of hydroxyethyl acrylate, 1 g of azobisisobutyronitrile, and 0.5 g of n-octyl mercaptan are uniformly mixed at room temperature to obtain a monomer mixture; in a nitrogen protective atmosphere, 1200 g of toluene is first heated to 65° C. in a water bath, and then the monomer mixture is added dropwise to the toluene under a heat preservation and stirring state, and the dripping is completed in 30 minutes. After the dripping is completed, the polymerization reaction is continued for 9 hours by heat preservation and stirring, and 175 g of a chlorobenzene solution of toluene-2,4-diisocyanate (2,4-TDI) with a solute mass fraction of 10.5% and 0.1 g of dibutyltin dilaurate are added to the obtained reaction system at one time, and the grafting reaction is continued at 50° C. in a nitrogen protective atmosphere with a heat preservation and stirring state for 1 hour, and then the reaction system is cooled to room temperature and left to stand for 24 hours. The resin product in the obtained reaction system is precipitated and precipitated from the solvent, and the resin product is filtered out and fully washed with toluene as an intermediate product;
[0036] The intermediate product obtained above was added to 1000 g of toluene, and heated to 55° C. in a water bath with stirring in a nitrogen atmosphere until the intermediate product was fully dissolved. Then, 25 g of hydroxyethyl acrylate, 0.1 g of dibutyltin dilaurate, and 0.1 g of p-hydroxyanisole were added thereto. The mixture was continued to react for 45 minutes at 55° C. in a nitrogen atmosphere with stirring. The mixture was cooled to room temperature and allowed to stand for 24 hours. The resin product in the reaction system was precipitated from the solvent. The resin product was filtered out and fully washed with ethanol. Then, the mixture was fully dried at 80° C. to obtain a reactive polymer grafted with a side group.
[0037] Preparation of energy-saving low-temperature light-curing powder coatings:
[0038] After the reactive polymer grafted with side groups prepared in the comparative example is crushed to 180-200 meshes, 100 parts of the reactive polymer grafted with side groups, 2 parts of leveling agent BYK-358N, 0.5 parts of ultraviolet light absorber UV-360, 0.5 parts of DF360 defoamer, and 1 part of free radical photoinitiator benzophenone are added to a high-speed stirrer at 900 rpm and stirred for 30 minutes.
[0039] Comparative Example 2
[0040] When preparing a reactive polymer grafted with side groups, "triphenylmethane triisocyanate" is replaced with an equal molar amount of "diphenylmethane-4,4-diisocyanate (MDI)", and the remaining components and operations are the same as in Example 1:
[0041] Preparation of reactive polymers grafted with side groups:
[0042] 50g of methyl methacrylate, 8g of n-butyl acrylate, 11g of hydroxyethyl acrylate, 1g of azobisisobutyronitrile, and 0.5g of n-octyl mercaptan are uniformly mixed at room temperature to obtain a monomer mixture; in a nitrogen protective atmosphere, 1200g of toluene is first heated to 65°C in a water bath, and then the monomer mixture is added dropwise to the toluene under a heat preservation and stirring state, and the dripping is completed in 30 minutes. After the dripping is completed, the polymerization reaction is continued for 9 hours by heat preservation and stirring, and 180g of a chlorobenzene solution of diphenylmethane-4,4-diisocyanate (MDI) with a solute mass fraction of 14.5% and 0.1g of dibutyltin dilaurate are added to the obtained reaction system at one time, and the grafting reaction is continued at 50°C under a nitrogen protective atmosphere and a heat preservation and stirring state for 1 hour, and then the reaction system is cooled to room temperature and left to stand for 24 hours. The resin product in the obtained reaction system is precipitated and precipitated from the solvent, and the resin product is filtered out and fully washed with toluene as an intermediate product;
[0043] The intermediate product obtained above was added to 1000 g of toluene, and heated to 55° C. in a water bath with stirring in a nitrogen atmosphere until the intermediate product was fully dissolved. Then, 25 g of hydroxyethyl acrylate, 0.1 g of dibutyltin dilaurate, and 0.1 g of p-hydroxyanisole were added thereto. The mixture was continued to react for 45 minutes at 55° C. in a nitrogen atmosphere with stirring. The mixture was cooled to room temperature and allowed to stand for 24 hours. The resin product in the reaction system was precipitated from the solvent. The resin product was filtered out and fully washed with ethanol. Then, the mixture was fully dried at 80° C. to obtain a reactive polymer grafted with a side group.
[0044] Preparation of energy-saving low-temperature light-curing powder coatings:
[0045] After the reactive polymer grafted with side groups prepared in the comparative example is crushed to 180-200 meshes, 100 parts of the reactive polymer grafted with side groups, 2 parts of leveling agent BYK-358N, 0.5 parts of ultraviolet light absorber UV-360, 0.5 parts of DF360 defoamer, and 1 part of free radical photoinitiator benzophenone are added to a high-speed stirrer at 900 rpm and stirred for 30 minutes.
[0046] The horizontal fluidity of the powder coatings prepared in the above-mentioned embodiments and comparative embodiments was tested respectively: 1.5 g of the powder coating was taken and pressed into a powder coating test piece with a thickness of 6 mm and a diameter of 12.7 mm in a steel sample press, and the test piece was placed flat on a constant temperature hot plate at 150°C (a thin layer of release agent was coated on the hot plate), and when the test piece melted and diffused outward on the hot plate until it no longer continued to flow and diffuse (the area of the hot plate was large enough), the diameter of the molten material of the test piece on the hot plate was measured at this time (three samples of the powder coating of each embodiment or comparative embodiment were tested and the average was taken), and the results are shown in Table 1;
[0047] The powder coatings prepared in the above-mentioned embodiments and comparative embodiments were subjected to photocuring molding: the powder coatings were evenly coated on the steel substrate by an electrostatic spray gun, with a coating thickness of about 100µm, and the obtained coating film was first heated at 100°C for 10 minutes to melt, and then UV irradiation (wavelength 395nm, intensity 60W / cm², vertical irradiation of 10cm between the coating film and the UV light source (high-pressure mercury lamp), irradiation curing time 2 minutes) was turned on to achieve photocuring of the coating film. After the photocured coating film was fully cooled, the hardness of the photocured coating film was tested according to GB / T6739-2006 "Determination of film hardness of paint and varnish pencil method" (three samples of the photocured coating film of each embodiment or comparative embodiment were measured, and the average was taken), and the adhesion of the photocured coating film was tested according to GB / T9286-1998 "Scratching test of paint and varnish film" (three samples of the photocured coating film of each embodiment or comparative embodiment were measured, and the average was taken), and the results are shown in Table 1.
[0048] Table 1
[0049]
[0050] It can be seen from Table 1 that when the triphenylmethane triisocyanate molecule is used as the graft of the main chain of the photocurable resin in this scheme, it has obvious advantages in fluidity and has very ideal film-forming and leveling properties during the photocuring process.
[0051] When a single benzene ring structure is used as the grafted side chain of the main chain of the photocurable resin in Comparative Example 1, the resin fluidity is obviously insufficient compared with this solution under the same test conditions. The applicant believes that one of the important reasons is that the benzene ring group grafted on the resin has a conjugated π electron system, and the benzene rings on different main chain molecular chains interact with each other π-π, which strengthens the interaction between the molecular chains, making the overall melt viscosity of the resin larger and the fluidity insufficient. This can also be seen from Comparative Example 2: the powder resin of Comparative Example 2 is worse than that of Comparative Example 1 in leveling. The applicant believes that this is because the grafted structure of Comparative Example 2 has a diphenyl structure, which makes it easier for different resin main chains to interact with each other through side groups, which further strengthens the interaction between the resin main chains, resulting in a higher overall melt viscosity of the resin.
[0052] In Examples 1 and 2 representing the present scheme, triphenylmethane triisocyanate molecules are selected as grafts on the main chain of the photocurable resin. Since the three benzene rings of the triphenylmethane triisocyanate molecule are connected to the same carbon atom, the three benzene rings may form a structurally regular and stable three-dimensional structure through π-π interactions. That is, the mutual constraints between the three benzene rings limit the mobility of the benzene rings, making it no longer easy for the benzene rings to interact with external benzene rings. Therefore, the interaction between the main chains of the polymer molecules in the photocurable resin is effectively reduced, the melt viscosity of the resin is reduced, and the fluidity is increased, so that the leveling property during low-temperature curing is more ideal.
Claims
1. An energy-saving low-temperature light-curing powder coating, characterized in that: The low-temperature light-curing powder coating comprises the following components in parts by weight: 100 parts of reactive polymer grafted with side groups Leveling agent 0.5~2 parts 0.2-1 part of UV absorber Defoaming agent 0.2~0.5 parts 1 to 3 parts of photoinitiator, The preparation method of the reactive polymer grafted with side groups is as follows: first, the acrylate monomer, the first functional acrylic monomer, the free radical initiator and the chain transfer agent are fully mixed, and then added dropwise to the first solvent for polymerization reaction. After the polymerization reaction for a period of time, an excess of triphenylmethane triisocyanate and a first catalyst are added to the first solvent for grafting reaction; after the grafting reaction is completed, the first separation and purification operation is performed, and the obtained intermediate product is fully washed and dispersed in the second solvent; then, the second functional acrylic monomer and the second catalyst are added to the second solvent to continue the reaction. After the reaction is completed, the second separation and purification is performed, and the obtained resin product is fully washed and dried.
2. The energy-saving low-temperature light-curing powder coating according to claim 1, characterized in that: The acrylic acid ester monomer is n-butyl acrylate, methyl methacrylate or butyl methacrylate.
3. The energy-saving low-temperature light-curing powder coating according to claim 1, characterized in that: The first functional acrylic monomer is acrylic acid, glycidyl methacrylate or hydroxy acrylate.
4. The energy-saving low-temperature light-curing powder coating according to claim 1, characterized in that: The second functional acrylic monomer is acrylic acid, glycidyl methacrylate or hydroxy acrylate.
5. The energy-saving low-temperature light-curing powder coating according to claim 1, characterized in that: The molar ratio of the acrylate monomer, the first functional acrylic monomer, and the triphenylmethane triisocyanate is 2-10:1:1.1-1.
2.
6. The energy-saving low-temperature light-curing powder coating according to claim 1, characterized in that: The molar ratio of the first functional acrylic monomer to the second functional acrylic monomer is 1:2 to 3.
5.
7. The energy-saving low-temperature light-curing powder coating according to claim 1, characterized in that: The reaction temperature of the polymerization reaction is 65° C. to 85° C., and the reaction time is 5 to 10 hours.
8. The energy-saving low-temperature light-curing powder coating according to claim 1, characterized in that: The reaction temperature of the grafting reaction is 50° C. to 65° C., and the reaction time is 0.5 to 1.5 hours.
9. The energy-saving low-temperature light-curing powder coating according to claim 1, characterized in that: The reaction temperature for adding the second functional acrylic monomer and the second catalyst to react is 50° C. to 65° C., and the reaction time is 0.5 to 1.5 hours.
10. The energy-saving low-temperature light-curing powder coating according to claim 1, characterized in that: The energy-saving low-temperature light-curing powder coating is prepared by fully mixing the reactive polymer grafted with side groups, the leveling agent, the ultraviolet light absorber, the defoaming agent, and the photoinitiator.